2019
DOI: 10.1089/ind.2019.29175.lbs
|View full text |Cite
|
Sign up to set email alerts
|

Bioprotective Culture: A New Generation of Food Additives for the Preservation of Food Quality and Safety

Abstract: Ensuring food quality and safety will remain a major challenge for the agri-food sector, due in large part to expected limits on the use of conventional microbiological barriers. There is an urgent need to develop new antimicrobial agents that are effective throughout the food manufacturing and distribution chain. The use of lactic acid bacteria and metabolites thereof to increase product shelf life has attracted much interest during recent years. Their potential as preservatives in many food matrices appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 108 publications
(109 reference statements)
1
40
0
Order By: Relevance
“…An interesting solution is the use of mycotoxin-binding microorganisms, especially lactic acid bacteria (LAB), but also propionic acid bacteria and Escherichia coli [231]. Literature data most often indicate the possibility of Fusarium mycotoxin removal by fermentation microorganisms, including bacteria that have the status of generally recognized as safe (GRAS) [232,233]. It has been shown that the mechanism responsible for the elimination of ZEA and its α-ZOL derivative by various strains of Lactobacillus rhamnosus is the adsorption of toxins to the bacterial cell wall, and not absorption into the cell [232].…”
Section: Biological Methodsmentioning
confidence: 99%
“…An interesting solution is the use of mycotoxin-binding microorganisms, especially lactic acid bacteria (LAB), but also propionic acid bacteria and Escherichia coli [231]. Literature data most often indicate the possibility of Fusarium mycotoxin removal by fermentation microorganisms, including bacteria that have the status of generally recognized as safe (GRAS) [232,233]. It has been shown that the mechanism responsible for the elimination of ZEA and its α-ZOL derivative by various strains of Lactobacillus rhamnosus is the adsorption of toxins to the bacterial cell wall, and not absorption into the cell [232].…”
Section: Biological Methodsmentioning
confidence: 99%
“…In this connection, bio-protective cultures offer a promising alternative to chemical preservatives ( Crowley et al, 2013 ). Bio-protective cultures are referred as food cultures, deliberately applied as live microorganisms to control the microbiological status in food ( EFFCA, 2018 ; Ben Said et al, 2019 ). As food additives, bio-protective cultures should have “generally recognized as safe” (GRAS) status and be included in the qualified presumption of safety (QPS) list in Europe ( Ben Said et al, 2019 ).…”
Section: Bio-protective Cultures and Other Yeast Interactionsmentioning
confidence: 99%
“…Bio-protective cultures are referred as food cultures, deliberately applied as live microorganisms to control the microbiological status in food ( EFFCA, 2018 ; Ben Said et al, 2019 ). As food additives, bio-protective cultures should have “generally recognized as safe” (GRAS) status and be included in the qualified presumption of safety (QPS) list in Europe ( Ben Said et al, 2019 ). In addition to yeast inhibition, bio-protective cultures should be able to proliferate in dairy products without affecting the performance of other starter and adjunct cultures, and without changing the technological and sensory quality of the products ( Schnürer and Magnusson, 2005 ).…”
Section: Bio-protective Cultures and Other Yeast Interactionsmentioning
confidence: 99%
“…Bioprotective cultures are microorganisms that show antimicrobial activity that inhibit either spoilage microorganisms or pathogens. Bioprotection involves adding specific cultures, that is live microorganisms to foods, to control its microbiological status without changing its technological and organoleptic properties (Ben Said et al., 2019). Bioprotection effects may include the production of organic acid, bacteriocins or other antimicrobials, competition for nutrients, cell‐to‐cell contact and niche effects (Cifuentes Bachmann & Leroy, 2015).…”
Section: Changes In the Selective Context Along The Production Chainmentioning
confidence: 99%